Exploring the factors influencing non-participation of women living with HIV/AIDS in empowerment projects attached to primary health care clinics, Tembisa, South Africa - Papole, Magdeline Kgomotso (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MPhil (Public Management and Planning))--University of Stellenbosch, 2010.